(untitled) (Journal of Science and Technology, 2016)
This paper presents evidence of some serious grammatical aberrations on nearly all the Frequency Modulation Stations (FM) in the Kumasi Metropolis. The paper argues that owing to the power of the electronic media, constant repetition of grammatical aberrations tend to exert a negative effect on learners, especially, the impressionable young ones. Some ways to tackle this sickening waywardness in the use of English have been suggested and attention drawn to the very sanctity of the word, as postulated, at least for our purposes, in John’s proclamation (1984). In the beginning was the Word, And the Word was with God, And the Word was God. This paper’s position, therefore, is that the fact of the Word being God attests to its very sanctity and the compelling need to avoid too many abusages and vulgarisms.